Transaktionskostnaders påverkan på inställningen till prissäkringsstrategier - Albertsson, Carl-Magnus; Ågren, Mathias (2020)
Agricultural businesses are exposed to many risk factors. For grain producers there are substantial risks which may affect income and costs. One way for producers to protect themselves is by hedging, which will help to stabilize income earnings. Futures- and forward contracts is one way for producers to do that. When establishing contracts, a lot of resources are needed and may lead to extended costs. The decision making is affected by uncertainty, trust, and relationship-specific investments.